Historical Influences on Contemporary Local Politics: The Case of Winnipeg - Wichern, P. (Urban History Review / Revue d'histoire urbaine, 1983)
This article argues that the claim that "the General Strike was the fundamental determinant in the modern political history of Winnipeg" is incorrect, not only because the claim cannot be substantiated properly with evidence, but because more extensive historical analysis suggests that civic boosterism is a better candidate for the accolade of "fundamental determinant" than the 1919 Strike. An alternative interpretation of the nature and significance of the Strike is provided, and civic boosterism is argued to be a good example of "the third face of power" proposed by Steven Lukes — that is, a dominant cultural value of a particular political economy. As such, the concept may have more widespread application as well as better summarizing the dominant influences in Winnipeg's civic political history.